Persistent organic compounds: A review - BANSAL, OM (European Journal of Applied Sciences, 2020)
Persistent organic pollutants (POPs) due to their lipophilic nature hydrophobicity and molecular stability are easily bioaccumulated in the animal tissues, food chains and because the resist to degradation in the environment persist for a long period is considered as silent killers. The developed as well as developing countries produces, utilizes and releases these pollutants in the environment, these pollutants are present in all the segments of the environment viz., atmosphere, sea water, groundwater, surface water, soils, air, sewage sludge, and sewage water, plants (crops) even in bovine, and mother milk. The major route of exposure to human beings is food consumption (vegetables, fruits, fishes, drinking water, beverages as well as bovine or mother’s milk). These pollutants are not only carcinogenic but are also responsible for endocrine disruption, diabetes, obesity, cardiovascular diseases, reproductive problems, behavioural changes, neurological and immunodeficiency disorder etc in the citizenry. Though these pollutants cannot be easily degraded there are few environmental’ processes mainly microbial or photolytic for the degradation of these pollutants to less toxic compounds. This review provides an overview of the concentration of these pollutants in drinking water, surface water, sediments, vegetables, fruits, fishes, and bovine, and mother milk and their impact on human. Few environmental processes for the degradation of these pollutants are also discussed in the review.